Selective infection of lower respiratory tract by respiratory viruses in children with recurrent respiratory tract infections. Issue 6331 (12th June 1982) - Isaacs, D; Clarke, J R; Tyrrell, D A; Valman, H B
Abstract : Thirty preschool children presenting with recurrent respiratory infections and their unaffected siblings were observed prospectively for a year. The index children experienced more episodes of acute respiratory infection than their siblings. Respiratory viruses were the major cause of respiratory infections. The index children had lower respiratory tract disease, predominantly wheeze, during 34% of proved respiratory virus infections compared with 11% of such infections experienced by the control children (p less than 0.02). Atopic children had an increased tendency to wheeze that did not reach significance, but atopy was not associated with increased susceptibility to respiratory infections.